1999
DOI: 10.2527/1999.7792554x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yucca schidigera on ruminal fermentation and nutrient digestion in heifers.

Abstract: In a replicated 3 x 3 Latin square experiment, six heifers (443 +/- 6.1 kg) fed a 61% barley grain:39% alfalfa silage diet (DM basis) were given intraruminal doses of powdered Yucca schidigera (YS). Doses of 0 (control), 20, or 60 g/d were given at 0800 daily. Ruminal content was sampled 0, 2, 4, and 6 h after dosing. Acidity, concentrations of reducing sugars, free amino acids, and peptides in the rumen were not affected (P > .05) by YS. Relative to control, ruminal ammonia concentration was reduced (P < .05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
168
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(199 citation statements)
references
References 23 publications
26
168
2
3
Order By: Relevance
“…Abreu et al (2004) and Hess et al (2004) found an increase in duodenal flow of microbial-nitrogen in sheep fed Sapindus saponaria fruit. However, Hristov et al (1999) did not obtain a significant effect of yucca saponin on microbial protein flow to the intestine in heifers. An increase of microbial nitrogen supply, efficiency of microbial-nitrogen supply, and faecal-nitrogen excretion with increasing levels of Sapindus rarak extract was observed, but this increase was not significant.…”
Section: Plants Containing Saponinsmentioning
confidence: 71%
“…Abreu et al (2004) and Hess et al (2004) found an increase in duodenal flow of microbial-nitrogen in sheep fed Sapindus saponaria fruit. However, Hristov et al (1999) did not obtain a significant effect of yucca saponin on microbial protein flow to the intestine in heifers. An increase of microbial nitrogen supply, efficiency of microbial-nitrogen supply, and faecal-nitrogen excretion with increasing levels of Sapindus rarak extract was observed, but this increase was not significant.…”
Section: Plants Containing Saponinsmentioning
confidence: 71%
“…They significantly decrease ruminal NH 3 concentration and increase that of propionic acid at the expense of acetate and butyrate (Abreu et al, 2004;Santoso et al, 2004b;Hristov et al, 1999). In agreement with the stoichiometry of ruminal fermentations, they significantly decrease methane production either in vitro (Lila et al, 2003;Hu et al, 2005) or in vivo (Santoso et al, 2004a).…”
Section: Saponinsmentioning
confidence: 81%
“…They have been shown to have hypocholesterolaemic, anticoagulant, anticarcinogenic, hepatoprotective, hypoglycaemic, immunomodulatory, neuroprotective, anti-inflammatory and anti-oxidant activities (Milgate and Roberts, 1995;Cheeke, 1999). In ruminants, dietary supplementation with saponins has been claimed to improve growth, feed efficiency and health (Mader and Brumm, 1987).…”
Section: Saponinsmentioning
confidence: 99%
“…Reductions in protozoal populations in the rumen of sheep and goats were also previously achieved by feeding dietary supplements of Yucca shidigera extracts (Hristov et al 1999) and of foliage from a variety of different sub-tropical leguminous trees (Leng et al 1992;Navas-Camacho et al 1992, 1993Chaudhary et al 1997;Newbold et al 1997;Teferedegne et al 1999). Saponins have been suggested as the active antiprotozoal agent in these plants (Newbold et al 1997).…”
Section: Discussionmentioning
confidence: 99%